2013
DOI: 10.3109/15376516.2012.757686
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicological impact of engineered nanomaterial exposure: mechanisms of immune cell modulation

Abstract: Engineered nanomaterials (ENM) are increasingly being utilized in many consumer products and various medical applications thereby leading to the potentiality of increased human exposures. Assessment of the adverse effects on the immune system is an important component for evaluating the overall health and safety of ENM. Tasked with eliminating pathogens and removing cancerous cells, the immune system is constantly functioning to maintain homeostasis. Small modifications to the immune system which may occur fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 87 publications
0
33
0
1
Order By: Relevance
“…These size-dependent differences in the immune response of GNS might be due to differences in internalization by phagocytes, since the efficient internalization of nanomaterials by phagocytes is reported to be partly size dependent. 40 Previous studies in our laboratory and others have demonstrated that pulmonary exposure to MWCNT induces submit your manuscript | www.dovepress.com…”
Section: Discussionmentioning
confidence: 99%
“…These size-dependent differences in the immune response of GNS might be due to differences in internalization by phagocytes, since the efficient internalization of nanomaterials by phagocytes is reported to be partly size dependent. 40 Previous studies in our laboratory and others have demonstrated that pulmonary exposure to MWCNT induces submit your manuscript | www.dovepress.com…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Moreover, several studies have attempted to address the toxicity associated with various routes of NP administration. 22,23 As such, few guidelines have been established and even fewer studies have been conducted to understand how protein coronas on nanomaterials are triggering NP toxicity. This may be attributed to a lack of comprehensive evaluation of 4,000,000 Notes: Different biological environments (serum-free medium versus complete medium supplemented with 10% serum) not only determine nanoparticle uptake levels but also influence intracellular nanoparticle location (Lysosome).…”
Section: Introductionmentioning
confidence: 99%
“…For example, cells of the immune system are activated in an inflammation. When the cells recognize a pathogen or, potentially an ENM, they secrete signaling molecules, such as cytokines, to attract more cells and destroy the invader (for reviews focusing on immunomodulation by ENM, see, e.g., Dobrovolskaia and McNeil, 2007;Wang et al, 2013). Thus, inflammation itself does not mean that a stressor is leading to immunotoxicity.…”
Section: Immune Systemmentioning
confidence: 97%